1990
DOI: 10.1017/s0305000900013076
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic significance of babbling: evidence from a tracheostomized infant

Abstract: The role of babbling in language development is not well understood. One source of evidence is the utterances of infants who were tracheostomized during the period in which they would normally have produced syllabic vocalization. We describe here the phonetic patterns and linguistic development of a girl called Jenny. She was tracheostomized and generally aphonic from o;5-1 ;8 but cognitively and socially normal, with near-normal comprehension of language. Acoustic analyses of Jenny's utterances following deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 29 publications
1
38
1
Order By: Relevance
“…Research has shown that children who are prevented from babbling by tracheostomy but who are language-normal do show lower rates of canonical babbling and delays in consonant acquisition (Bleile, Stark, & Silverman McGowan, 1993;Locke & Pearson, 1990). However, the present results demonstrate that the relationship between vocalization rate and number of different consonants is complex, nonlinear, and furthermore can differ between different groups of children.…”
Section: Discussioncontrasting
confidence: 56%
“…Research has shown that children who are prevented from babbling by tracheostomy but who are language-normal do show lower rates of canonical babbling and delays in consonant acquisition (Bleile, Stark, & Silverman McGowan, 1993;Locke & Pearson, 1990). However, the present results demonstrate that the relationship between vocalization rate and number of different consonants is complex, nonlinear, and furthermore can differ between different groups of children.…”
Section: Discussioncontrasting
confidence: 56%
“…This is true both for humans, who do not learn spoken language (or even babble normally) if they are deaf (87), and also for song birds (88). Production plays a role in normal language development; infants tracheostomized at the time at which they normally would babble show abnormal patterns of development that persist (89). These cases illustrate the strong dependency between perception and production and suggest why speech motor patterns learned early in life become difficult to alter later.…”
Section: Vocal Learning Unifies Perception and Productionmentioning
confidence: 99%
“…Recently, Clement and Koopmans-van Beinum [1995] compared 6 deaf with 6 hearing infants and found differences in their sound production even within their first half-year. A case study of a tracheotomized infant suggests that auditory experience is crucial to vocal learning [Locke and Pearson, 1990]. The subject was tracheotomized at 5 months and failed to babble or speak until the decannulation at 20 months of age.…”
Section: Introductionmentioning
confidence: 99%